Realitas Penerapan Literasi Digital bagi Mahasiswa FKIP Universitas Muhammadiyah Sidoarjo - Vevy Liansari; Ermawati Z Nuroh (International Consortium of Education and Culture Research Studies, 2018)
The development of the digital world can be used to further enhance the ability to find, use, summarize, evaluate, create and communicate information using digital technology. Digital literacy also with digital information literacy is the ability to understand and use information from a variety of digital sources. This article was motivated by difficulties in the implementation of student literacy and PEDAGOGY at the University of Muhammadiyah Sidoarjo. The fact of the current internet users has increased and the majority of the teenager. Internet usage by teenagers vary, not just used to looking for academic information, but also to build relationships through social networking sites. Therefore, this article will discuss the reality of the implementation of digital literacy in FKIP University of Muhammadiyah Sidoarjo.